Targeted mutation of mouse skeletal muscle sodium channel produces myotonia and potassium-sensitive weakness - Hayward, Lawrence J. (American Society for Clinical Investigation, 2008)
Hyperkalemic periodic paralysis (HyperKPP) produces myotonia and attacks of muscle weakness triggered by rest after exercise or by K(+) ingestion. We introduced a missense substitution corresponding to a human familial HyperKPP mutation (Met1592Val) into the mouse gene encoding the skeletal muscle voltage-gated Na(+) channel Na(V)1.4. Mice heterozygous for this mutation exhibited prominent myotonia at rest and muscle fiber-type switching to a more oxidative phenotype compared with controls. Isolated mutant extensor digitorum longus muscles were abnormally sensitive to the Na(+)/K(+) pump inhibitor ouabain and exhibited age-dependent changes, including delayed relaxation and altered generation of tetanic force. Moreover, rapid and sustained weakness of isolated mutant muscles was induced when the extracellular K(+) concentration was increased from 4 mM to 10 mM, a level observed in the muscle interstitium of humans during exercise. Mutant muscle recovered from stimulation-induced fatigue more slowly than did control muscle, and the extent of recovery was decreased in the presence of high extracellular K(+) levels. These findings demonstrate that expression of the Met1592Val Na(+) channel in mouse muscle is sufficient to produce important features of HyperKPP, including myotonia, K(+)-sensitive paralysis, and susceptibility to delayed weakness during recovery from fatigue.